Oral administration of Limosilactobacillus ingluviei C37 inhibits Campylobacter jejuni colonization in chicks - Murakami, Aito; Watanabe-Yanai, Ayako; Iwata, Taketoshi; Namai, Fu; Sato, Takashi; Fujii, Tadashi; Tochio, Takumi; Khempaka, Sutisa; Shimosato, Takeshi (Frontiers in Microbiology, 2024)
As the global population continues to grow, so too does the demand for poultry meat. However, the concurrent increase in the prevalence of drug-resistant bacteria has stimulated interest in the search for alternatives to antibiotics in poultry and livestock agriculture. One potential strategy is the use of probiotics. In this study, we showed that prophylactic oral administration of Limosilactobacillus ingluviei C37 (LIC37) reduced Campylobacter jejuni colonization of the cecum in cage-raised chicks, without causing significant changes in the overall diversity of gut bacteria. Further, the abundance of Blautia, another genus of probiotic bacteria, increased in the gastrointestinal tract following ingestion of LIC37 by chicks. These findings suggest that LIC37 could potentially be used as a novel probiotic agent against C. jejuni in livestock production.